Correspondence: risk factors of acute respiratory infection in under-fives in a rural hospital of Central India - Authors' reply - Amar Taksande; Mayuri Yeole (Hygeia Press di Corridori Marinella, 2016)
Dear Editor, We thank the authors for their interest and comments on our paper. They have raised some very valid points.   This corrispondence refers to the following article: Taksande AM, Yeole M. Risk factors of Acute Respiratory Infection (ARI) in under-fives in a rural hospital of Central India. J Pediatr Neonat Individual Med. 2016;5(1):e050105. doi: 10.7363/050105. Comments can be found in the following article: Mandal A, Sahi PK. Correspondence: risk factors of acute respiratory infection in under-fives in a rural hospital of Central India. J Pediatr Neonat Individual Med. 2016;5(2):e050207. doi: 10.7363/050207.